Hypothalamic Structure and Function in Alzheimer’s Disease and Lewy-Body Dementia: A Systematic Review and Meta-Analysis - Axel AS Laurell; Sita N Shah; Masoud Rahmati; John T O’Brien; Benjamin R Underwood (BJPsych Open, 2025)
Aims: Changes to sleep, weight, and endocrine function are common in Alzheimer’s disease (AD) and Lewy-body dementia (LBD). The cause of these is not known, but they may be related to hypothalamic neurodegeneration. Our aim was to assess whether hypothalamic volume is reduced in people with AD and LBD, and whether hypothalamic volume is associated with these common symptoms.